Advancing Rural Education in Bangladesh: The Strategic Role of NGOs in Expanding Access and Addressing Developmental Challenges - Md. Sobuj Mia; Md. Yeasir Arafat; Md. Ismail Hossen Imran; Fahmida , Fahmida; Mst. Sumaiya Akter; Tanvir Ahmed (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
SDG 4 stands for giving everyone good and equal education and chances to keep learning throughout life. Non-Governmental Organizations (NGOs) play an undeniable role in tackling educational challenges in rural Bangladesh, where poverty, lack of awareness, poor infrastructure, and social barriers limit access to quality education. This study reviews the work of NGOs over recent decades to understand how they have helped improve education in rural communities. It examines how NGOs have addressed issues such as enrollment, literacy, gender equality, community involvement, and sustainability. The findings show that NGOs have increased school attendance and literacy through community-based non-formal education, scholarships, teacher training, life skills programs, and digital learning initiatives. They have also promoted gender equality and encouraged local communities to take part in education programs. Despite their success, NGOs face challenges including funding shortages, weak infrastructure, technological gaps, social resistance, and coordination difficulties with government agencies. The study offers practical suggestions for improving collaboration with the government, securing funding, enhancing teacher support, expanding digital access, and building climate resilience into education programs. Overall, the study provides clear insights for policymakers, educators, and development practitioners aiming to strengthen rural education.